PENGARUH SOCIAL MEDIA MARKETING TERHADAP MINAT BELI MAHASISWA SAAT PANDEMI COVID-19 DI BALI - Kurniawan, Ida Bagus; Kurniawati, Natalia Sri Endah; Puniawan, I Made Endra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The Covid-19 pandemic is currently happen gives a several boundaries to the society. The society asked to avoid the crowd for reduce the spreading of the virus. College students as a part of society are also affected. College students must studying online and reduce the activities outside the house include shopping. With the development of technology, now shopping can be done using social media. There are various forms of social media marketing that was done by the producers. The marketing effort was done to increase the buying interest of consumer. This research aims to know the influence of social media marketing on buying interest of the college student during the Covid-19 pandemic in Bali. This research was conducted by distributing online questionnaires to 100 college students. The method that used in this research is multiple linear regression to determine the effect of several variables on other variables. Based on the research that has been done, it is found that from the social media marketing variables tested, the communication variable and the connection variable have a partial effect on college student buying interest during the Covid-19 pandemic in Bali , while the context and collaboration variables have no effect on student buying interest. And if tested together, the variables context, communication, connection and collaboration have a simultaneous effect on college student buying interest during the Covid-19 pandemic in Bali.